Synovial Chondromatosis and Chondrosarcoma: A Diagnostic Dilemma. (2003) - Sperling, Brita L.; Angel, Steven; Stoneham, Grant; Chow, Vance; McFadden, Andrew; Chibbar, Rajni
Abstract : Purpose : The progression of synovial chondromatosis to chondrosarcoma is very rare. Distinction between these two entities may be difficult on histology alone, and should be based on clinical, radiographic and microscopic evidence. Immunohistochemical markers that would facilitate differentiation between synovial chondromatosis and chondrosarcoma are currently being investigated. Patients : We describe the cases of two patients who presented with synovial chondromatosis and progression to synovial chondrosarcoma during periods of 7 and 11 years. Several biopsies and resected specimens demonstrated synovial chondromatosis before a diagnosis of chondrosarcoma was made. Method : We have examined five markers (Bcl2, Ki67, p27, p16, and p53) in all specimens from these cases, as well as known cases of chondromatosis and chondrosarcoma for control purposes. Results : We found increased expression of Bcl2 in benign chondromatosis compared to synovial or central chondrosarcomas. Discussion : Distinction between chondromatosis and its progression to low grade chondrosarcoma is difficult at histological level, and must involve incorporation of clinical and radiographical data. Although preliminary, our study suggests that reduced or absent expression of Bcl2 is associated withmalignant transformation of chondromatosis.